Two new species of Crassitegula (Sebdeniaceae, Sebdeniales, Rhodophyta) extend the diversity and biogeographic range of the genus to the Caribbean and Mediterranean seas - Craig W. Schneider; Line Le Gall (European Journal of Taxonomy)
Crassitegula (Sebdeniaceae, Sebdeniales) is a relatively new genus of red algae, currently consisting of three species, that was first described based on a western Atlantic species in 2006. In the present paper, two species of Crassitegula are newly described from the Caribbean and Mediterranean seas, both being first detected using COI-5P barcoding, then followed by phylogenetic analysis. Crassitegula bouchetii L.Le Gall & C.W.Schneid. sp. nov. and C. garyi L.Le Gall & C.W.Schneid. sp. nov. represent the fourth and fifth species in the genus, which, prior to this study, has been confined to Bermuda (western Atlantic) and Lord Howe Island (Australia). Crassitegula garyi, from France, Corsica and Italy in the north-central Mediterranean, has a strap-shaped habit reminiscent in part of C. walsinghamii C.W.Schneid., C.E.Lane & G.W.Saunders and C. laciniata C.W.Schneid., Popolizio & C.E.Lane, whereas C. bouchettii is presently known only as small, peltate, kidney-shaped blades that possibly represent immature specimens.